The Development of Human Resources of Hospitality Sector Certified Competence Siantar City, Simalungun Regency - Trisnawaty (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
This study was conducted to find out how the development of human resources in the field of hospitality in the city of Siantar Simalungun district, North Sumatra Province. The method used in this study is a qualitative method with descriptive research type which explains the actual conditions that occur in the field with data collection techniques through observation, interview and documentation. Based on the results of the research can be known that the development of human resources in the field of hospitality has not been maximized and there is no competence certification for employees who work in existing hotels in Balige City, so expect the role of government and employers to care about it so that operational quality in service to Guests can do better.